From tough times to better times: feminism, public policy, and new labour politics in Britain - Bashevkin, Sylvia (2000)
A series of significant internal changes transformed the British Labour Party in the years following 1983. This article is among the first to probe the women and politics dimension of these reforms, focusing on three main questions: first, what benefits accrued to Labour and organized feminism as a result of changes introduced after 1983? Second, what costs were incurred by both sides due to party reform, and how might these disadvantages affect their longer-term relationship? And third, how were initial New Labour government decisions viewed by women's group activists? The article concludes that although the 1997 elections did not produce a policy nirvana for British feminism, their initial effects augured reasonably well for movement interests. - Reproduced
Keywords: British Labour Party; Political parties - Great Britain; Public policy - Great Britain; Women in politics - Great Britain; Women in politics